Guidance Counseling Can Reduce Inequality in University Enrollment in Germany: Results from a Randomized Controlled Trial - Irena Pietrzyk; Melinda Erdmann; Juliana Schneider; Marita Jacob; Marcel Helbig (Sociology of Education, 2025)
Guidance counseling is well known to foster enrollment in higher education among students from low social origins in the United States and Canada. However, because students in these North American countries face obstacles that do not exist in many European countries, generalizing previous findings to the European context is difficult. Against this background, we use a randomized controlled trial to investigate guidance counseling in Germany. Our results reveal that individuals from low social origins are more likely to enroll in higher education due to the program. Furthermore, we find substantial effect heterogeneity across social origin groups. Due to the program, individuals from high social origins enroll less frequently in higher education and more frequently in vocational training. Based on these opposing effects across social origin groups, we find that the program reduces inequality in higher education enrollment by approximately 700.167empercent.
Keywords: 330; counseling; inequality; university enrollment; randomized controlled trial; social origin